Three‐dimensional quantification of the relationship between the upper first molar and maxillary sinus. Issue 3 (25th March 2022) - Regnstrand, Tobias; Ezeldeen, Mostafa; Shujaat, Sohaib; Ayidh Alqahtani, Khalid; Benchimol, Daniel; Jacobs, Reinhilde
Abstract: Objectives: The present study aims to describe the relationship between upper first molar roots and maxillary sinus, for the first time with a truly three‐dimensional approach. Methods: From a retrospective cone‐beam computed tomography (CBCT) sample of the upper jaw, a total of 105 upper first molars in contact with maxillary sinus from 74 patients (male 24, female 50, mean age 42) were included in the present study. Segmentation of the upper first molar and maxillary sinus in CBCT was performed utilizing a semiautomatic livewire segmentation tool in MeVisLab v.3.1. The segmentations were analyzed in 3‐matic Medical 20.0 for root volume and the contact area between upper first molar roots and maxillary sinus. Analysis of variance test was applied to detect statistically significant differences between the roots. Results: The palatal root had the largest contact area with maxillary sinus 27.8 ± 21.4 mm 2 (20% of the root area) followed by the mesiobuccal 20.5 ± 17.9 mm 2 (17% of the root area) and distobuccal root 13.7 ± 12 mm 2 (14% of the root area). A significant difference in the contact area of the different roots of the upper first molar was seen. Conclusions: This study showed that 70% of the upper first molars were in contact with the maxillary sinus. The palatal root had on average a fifth of its root surface in contact with the sinus, while for mesiobuccal this was a sixth of its root surface and distobuccal roots this was somewhat less. The true 3D relationship could help to better understand maxillary anatomy in relation to occurring pathologies and treatment planning in this area.